E-commerce dan Startup: Wujud Inovasi Keberlanjutan Bisnis Di Era Industri 4.0 - Marhawati Marhawati; A Azizah; Erwina Erwina; Raflianto Raflianto (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2023)
The importance of innovating and creating in the era of the industrial revolution 4.0 we are required to be smarter in innovation in order to get the highest benefits from new emerging technologies. For this reason, this study will present a literature review of the role of e-commerce and startups as a form of business sustainability innovation in the industrial era 4.0. The method used in this research is through conceptual and theoretical deepening as well as the collection of information and data related to e-commerce starup and innovation   as well as supporting data from various sources. The results of the study stated that it is appropriate for us to move from traditional business to digital-based business by keeping up with the times, one of which is by utilizing e-commerce  and startups as business innovations that are able to compete in globalization. The current solution is the availability of counseling and training by institutions or institutions regarding digital business for people who do not understand information technology. One thing in Indonesia that makes optimism is the number of strong entrepreneurial spirits, so that  Indonesian e-commerce will only get stronger in the future, one example is Tokopedia.